Produksi Menurut Pemikiran Muhammad Abdul Mannan - Mutmainah, Mutmainah; Hasan, Hasan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Producing a product in economic activities requires a production process that allows consumption, distribution or exchange of goods and services. The aim of this research is to find out Islamic Economics Theory and Practice related to production according to Muhammad Abdul Mannan's Perspective. This research is a library research study. There are two data sources, these are (1) primary data sources, and (2) secondary data sources. Data collection methods include: direct quotations and indirect quotations. Meanwhile, the data analysis is a content analysis technique. The results of this research are Production in Islamic Economics Theory and Practice according to Muhammad Abdul Mannan's perspective, showing that production prioritizes the concept of the welfare of the people which is guided by the Koran and Hadith, by adhering to the basic principles of Islamic economics including, faith, prophethood, government and results so as to create justice and prosperity for the present and the future. In order for production to continue to grow, it is influenced by several factors, including: Land, labor, capital and organization